Educação sexual na escola currículo e práticas - Fiorini, Jéssica Sampaio (Editora Oficina Universitária, 2020)
How does the school deal with issues related to sexuality? Are there obstacles to promoting sex education in schools? How could the school contribute to overcoming taboos and prejudices regarding gender and sexuality issues? This book contains the result of a Master's research carried out within the scope of the Graduate Program in Education at FFC/UNESP - Marília. It addresses the issue of sex education in the early years of elementary school, bringing the main contents and discussions on this topic, in addition to important reflections on the school curriculum and on teachers' practices in relation to issues related to sexuality. It is our expectation to share studies that can contribute to a greater understanding of the theme of sex education, especially in the context of childhood, in addition to collaborating with the modification of decision-making on the subject in question.